PWE-037 Acute severe ulcerative colitis (ASUC) outcomes aren't altered by admission to a tertiary referral centre. (8th June 2018) - Manship, Thomas; Grant, Rebecca; Jagger, Fiona; Lynch, Ruairi; Lees, Charlie; Satsangi, Jack; Arnott, Ian; McGowan, Aaron
Abstract : Introduction: First-line treatment for ASUC with IV steroids is routinely given in UK hospitals. We sought to establish if initial treatment in a tertiary referral centre affected outcome. We examined all admissions with ASUC within Lothian and compared outcomes between those initially treated at the tertiary referral centre: Western General Hospital (WGH) and those treated at the other two acute hospitals in the health trust: Royal Infirmary of Edinburgh (RIE) and St. John's Hospital (SJH). We assessed response to steroids and second-line medical therapy and the likelihood of requiring surgery during the index admission. Methods: Admissions to NHS Lothian were identified using the ICD-10 code K51 between November 2013 and November 2016. If a patient was admitted more than once during this time only the first admission was used. 159 patients were included. 105 (105/159; 66.0%) were admitted to WGH. 14 (14/159; 8.8%) were admitted to RIE and 40 (40/159; 25.2%) were admitted to SJH. Female: male split was 60 (37.7%):99 (62.3%). Mean age at admission was 41.7 years (range 16.3–86.75). Results: 71.4% (75/105) were successfully treated with IV steroids at WGH compared with 63.0% (34/54) at RIE and SJH (p=0.364; OR=1.471). 37.0% (20/54) of patients treated for ASUC at the other hospitals in NHS Lothian required transfer to WGH for further management. There was wide variation in the proportion of ASUC patients referred from the two referring hospitals: 45% (SJH, 18/40) and 14.2% (RIE, 2/14). There was no significant difference in the proportion of patients requiring medical rescue therapy (Infliximab or Ciclosporin) when comparing those admitted to WGH 23.8% (25/105) and those admitted to RIE and SJH 33.3% (18/54) (p=0.1412; OR=0.625). Of those requiring second line medical therapy 48.0% (12/25) responded in the tertiary centre compared with 50.0% (9/18) in those admitted to other hospitals, and therefore did not require surgery (p=0.6609; OR=0.923). At WGH 16.7% (5/30) required surgery after failing IV steroids without being given second line medical therapy. Compared with 10% (2/20) of those transferred from surrounding hospitals (p=0.8029; OR=1.8). Conclusions: In Lothian, although there is no statistical difference in response to IV steroids whether treatment was started in a tertiary referral centre or not, there was a trend towards a greater success at WGH. There was no statistical difference in response to second line medical therapy between the two groups. Although numbers are small there is a trend to patients in the tertiary referral centre being more likely to proceed directly to surgery upon steroid failure. This could be due to the input of the surgical team at an earlier stage.